A New Source for the History of Eighteenth-Century Bookselling: The Journal of Stephen Armitage. (17th March 2020) - King, Patrick J
Abstract: This article brings to light and discusses a rare survival, the journal of an eighteenth-century bookdealer, identified here as the Irish seller Stephen Armitage (d. 1799). The journal details business and leisure activities in England and Ireland between 1776 and 1784 and includes ten contemporary topographical plates pasted in.